An evaluation of information transfer through the continuum of surgical care: a feasibility study. - Nagpal, K; Vats, A; Ahmed, K; Vincent, C; Moorthy, K (2010)
OBJECTIVE: To evaluate information transfer and communication (ITC) across the surgical care pathway with the use of Information Transfer and Communication Assessment Tool for Surgery (ITCAS). BACKGROUND: Communication failures are the leading cause of surgical errors and adverse events. It is vital to assess the ITC across the entire surgical continuum of care to understand the process, to study teams, and to prioritize the phases for intervention. METHODS: Twenty patients undergoing major gastrointestinal procedures were followed through their entire surgical care, and ITC process was assessed using ITCAS. ITCAS consisted of 4 checklists for 4 phases of the surgical care. RESULTS: ITC failures are distributed across the entire surgical continuum of care. Preprocedural teamwork and postoperative handover phases have the maximum number of ITC failures (61.7% and 52.4%, respectively). Moreover, it was found that information degrades as it crosses from one phase to another. Of patients, 75% had clinical incidents or adverse events because of ITC failures. CONCLUSIONS: The study demonstrated that ITC failures are ubiquitous across surgical care pathway and there is an imminent need to modify current ITC practices. Standardization of ITC through use of checklists, protocols, or information technology is essential to reduce these communication failures.